OUTCOMES OF SUPERIORLY BASED NASOLABIAL ISLAND FLAPS IN NASAL SKIN CANCER RECONSTRUCTION: A REPORT OF 20 CASES (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical characteristics and determine the long-term functional and aesthetic efficacy of the superiorly based nasolabial island flap in nasal reconstruction following skin cancer resection.Subject and method: A descriptive case series was conducted on 20 patients with nasal skin cancer who underwent wide local excision and immediate reconstruction at Ho Chi Minh City Oncology Hospital from June 2022 to October 2025.Results: The mean age was 66 ± 11.4 years old, with a female predominance (80%). BCC was the primary histological type (95%). Stage T2 tumors were most common (75%). The mean flap area was 18.7 ± 10.1cm². A 100% flap survival rate was achieved. Early complications (venous congestion, superficial necrosis) occurred in 15% of cases and resolved spontaneously. No recurrence or lymph node metastasis has been recorded. Aesthetic outcomes reached 100% "Excellent" and "Good" ratings.Conclusion: The superiorly based nasolabial island flap is a feasible option, demonstrating favorable initial outcomes in this case series. Its wide rotation arc and superior reach enable coverage of all nasal subunits. By tunneling the pedicle subcutaneously, this technique facilitates a single-stage procedure, thereby optimizing treatment costs and patient recovery.
Keywords: Nasal skin cancer, superiorly based nasolabial island flap, basal cell carcinoma, squamous cell carcinoma.